Tobacco Cessation: Are Oral Cancer Patients Ready for It - Sujatha, S; Iyengar, Asha; Pruthvish, S; Priyadharshini, R (Indian Journal of Medical and Paediatric Oncology, 2019)
Aims: The objective was to examine the predictors of readiness to quit tobacco among oral potentially malignant disorder (OPMD) and oral cancer (OC) patients in dental health care setting. Settings and Design: Two hundred and seven patients diagnosed with OC or OPMDs comprising 153 males and 54 females, with mean age being 52.2 years, with varying levels of addiction formed the study group. Subjects and Methods: Readiness to quit tobacco as measured by the ladder of change and the single-item readiness question was significantly correlated with measures of perceived risk. Statistical Analysis Used and Results: Pearson’s correlations showed that readiness to quit tobacco was significantly correlated with the participant’s perception of his or her health compared with other tobacco users of the same age (P < 0.005). Readiness to quit was positively correlated with the degree to which participants felt that their oral condition is related to their tobacco use (P < 0.001), how much their general health is affected by tobacco use (P < 0.01), and how much quitting tobacco could influence their health positively (P < 0.001). Post hoc analyses showed that readiness to quit was also significantly and negatively correlated with nicotine addiction (P < 0.001) and decisional balance scores (P < 0.01). Conclusions: There is an urgent need for tobacco risk assessment, intervention, and education with this population of patients, and hence, health professionals can play a significant role in motivating and assisting to quit.
Keywords: Oral cancer; oral potentially malignant disorder; readiness to quit tobacco; risk prediction; tobacco cessation